TINGKAT KEKUATAN ANTIOKSIDAN DAN KESUKAAN MASYARAKAT TERHADAP TEH DAUN GAHARU (Aquilaria malaccensis Lamk) BERDASARKAN POHON INDUKSI DAN NON-INDUKSI - Putri Andaria Nasution; Ridwanti Batubara; Surjanto Surjanto (Program studi Kehutanan USU, 2015)
During the long enough harvesting cycle, aloes leaves can be used as medicine and poured drink that has a role as antioxidants. This research was to study the societies predilection level to aloes tea and the strength of aloes leaves antioxidant activity based on the induction and non-induction tree. This research used 1,1-diphenyl-2-picrylhydrazil (DPPH) method with the observation parameter are the percentage of free radicals submerged at the 60th minute with different concentration (40 ppm, 60, ppm, 80 ppm and 100 ppm) and the value of IC50 (Inhibitory Concentration) was analyzed by regression similarity. The result of antioxidant activity observation by using the UV-Visible light Spectrophotometer at the swell length of 516 nm showed that the result of aloes leaves simplicia ethanol extract (EESDG) induction and non-induction had IC50 value of 99.42 ppm and 70.40 ppm. The result of EESDG had a significantly antioxidant activity. The hedonic test results showed that the stroge of aloes leaves for 0 month were the most predilection in the society due to the taste at induction treatment with the taste score 3.83 but due to the aroma and colour, had the same value 3.10 and 3.83. Aloes leaves tea at the 2 month storage which the most predilection in society was at the non-induction treatment, by the score of taste, aroma and colour were 3.30, 2.80 and 3.80. Keywords: Aloes tea, antioxidant activity, induction and hedonic test.